Alloys and Composites of Polybenzoxazines Properties and Applications - Rimdusit, Sarawut; Jubsilp, Chanchira; Tiptipakorn, Sunan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2013)
This book provides an introduction to the unique and fascinating properties of alloys and composites from novel commercialized thermosetting resins based on polybenzoxazines. Their outstanding properties such as processability, thermal, mechanical, electrical properties as well as ballistic impact properties of polybenzoxazine alloys and composites make them attractive for various applications in electronic packaging encapsulation, light weight ballistic armour composites and bipolar plate in fuel cells.
Introduction to Commercial Benzoxazine Resins -- Polybenzoxazine Alloys -- Highly Filled Systems of Polybenzoxazine -- High Thermal Conductivity of BN-Filled Polybenzoxazine -- Natural Fiber Polybenzoxazine Composites -- Polybenzoxazine Composites for Ballistic Armor Applications -- Electrical Conductivity of Filled Polybenzoxazine.
Keywords: Chemistry; Polymers; Engineering design; Chemistry; Polymer Sciences; Ceramics, Glass, Composites, Natural Methods; Engineering Design